A genome-wide association study reveals that the glucosyltransferase OsIAGLU regulates root growth in rice. (1st November 2020) - Zhao, Jia; Yang, Bin; Li, Wenjun; Sun, Shan; Peng, Liling; Feng, Defeng; Li, Li; Di, Hong; He, Yongqi; Wang, Zhoufei
Abstract : OsIAGLU encodes a glucosyltransferase that regulates root growth in rice during the early post-germination period by influencing multiple hormone pathways. Abstract: Good root growth in the early post-germination stages is an important trait for direct seeding in rice, but its genetic control is poorly understood. In this study, we examined the genetic architecture of variation in primary root length using a diverse panel of 178 accessions. Four QTLs for root length ( qRL3, qRL6, qRL7, and qRL11 ) were identified using genome-wide association studies. One candidate gene was validated for the major QTL qRL11, namely the glucosyltransferase OsIAGLU . Disruption of this gene in Osiaglu mutants reduced the primary root length and the numbers of lateral and crown roots. The natural allelic variations of OsIAGLU contributing to root growth were identified. Functional analysis revealed that OsIAGLU regulates root growth mainly via modulating multiple hormones in the roots, including levels of auxin, jasmonic acid, abscisic acid, and cytokinin. OsIAGLU also influences the expression of multiple hormone-related genes associated with root growth. The regulation of root growth through multiple hormone pathways by OsIAGLU makes it a potential target for future rice breeding for crop improvement.